Prioritizing the Forces of Brain Drain: Perspectives of Nepali Youths - Chaudhary, Rajesh Kumar; Gautam, Keshav (Journal of Emerging Management Studies, 2026)
Purpose – This paper aims to provide the current scenario of the brain drain of Nepali youths. It also intended to investigate how poor governance, limited access to quality education, misplacement of talent and low occupational income affect the Nepalese brain drain.Design/methodology/approach – This research is quantitative in nature and adopted a descriptive and correlational design. 405 Nepali youths currently living abroad or planning to migrate to abroad were taken as the sample for study. The data were collected from structured questionnaire through both online and hard copies survey. The used questionnaire was developed on a five-point Likert scale.  The collected data were processed and output of data generated with aid of MS-Excel and SPSS.Findings and Conclusion – This paper finds that poor governance, low occupational income, and limited access to quality education are major causes of brain drain in Nepal. Although talent misplacement is still a known issue, its lack of statistical significance suggests that more concrete, structural variables have a bigger impact on migration decisions.Implications – This study applies the push-pull migration framework to Nepalese brain drain, identifying low income, weak governance, and poor education access as key push factors. Practically, it urges policymakers to prioritize wage reforms, education-labor alignment, and merit-based hiring. Public-private partnerships, skill industry investments, and reintegration programs are essential. A multi-stakeholder approach involving government, academia, and business is needed to reduce brain drain and leverage diaspora expertise for national development.